2022
DOI: 10.1029/2022jc018551
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Surface Oceanic Kinetic Energy Distributions From Drifter Observations and Numerical Models

Abstract: The geographical variability, frequency content, and vertical structure of near-surface oceanic kinetic energy (KE) are important for air-sea interaction, marine ecosystems, operational oceanography, pollutant tracking, and interpreting remotely sensed velocity measurements. Here, KE in high-resolution global simulations (HYbrid Coordinate Ocean Model; HYCOM, and Massachusetts Institute of Technology general circulation model; MITgcm), at the sea surface (0 m) and at 15 m, are compared with KE from undrogued a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 117 publications
(240 reference statements)
0
11
0
1
Order By: Relevance
“…In region A, the unfiltered horizontal velocity field (the orange line in Figure 3a) has a spectral peak at the inertial frequency (shown by the vertical black line in Figure 3) and at the semidiurnal frequency (shown by the vertical blue line in Figure 3), as well as additional peaks at various supertidal frequencies. These peaks are a feature of high‐resolution global models, perhaps caused by insufficient resolution of internal wave triads (Arbic et al., 2022; Savage et al., 2017). These peaks are associated with inertia‐gravity waves in LLC4320 (Torres et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In region A, the unfiltered horizontal velocity field (the orange line in Figure 3a) has a spectral peak at the inertial frequency (shown by the vertical black line in Figure 3) and at the semidiurnal frequency (shown by the vertical blue line in Figure 3), as well as additional peaks at various supertidal frequencies. These peaks are a feature of high‐resolution global models, perhaps caused by insufficient resolution of internal wave triads (Arbic et al., 2022; Savage et al., 2017). These peaks are associated with inertia‐gravity waves in LLC4320 (Torres et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it should be emphasized that our calculation of ε (Equation 7) following the modified slab model of Jing et al (2017) is only qualitative. In addition, Arbic et al (2022) found that low-frequency motions may vary quite substantially between the surface and 15-m depth, questioning the slab-model assumption. However, according to Jing et al (2017), the slab-model assumption is adequate for the present qualitative analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Model output from global HYCOM simulations has been validated extensively against moorings (Luecke et al, 2020), altimetry (Buijsman et al, 2016(Buijsman et al, , 2020Shriver et al, 2012), drifters (Arbic et al, 2022), and other models (Arbic et al, 2022;Savage et al, 2017). While these comparisons are favorable for the subtidal, inertial, and tidal bands, the 4-km simulations are still deficient in resolving motions at supertidal frequencies (Luecke et al, 2020;Savage et al, 2017;Siyanbola et al, 2023).…”
Section: Modelmentioning
confidence: 99%
“…The appearance of solitary‐like waves in hydrostatic models (Jensen et al., 2020) has been attributed to numerical dispersion that mimics the nonhydrostatic dispersion (Vitousek & Fringer, 2011). Global ocean models do simulate internal waves at supertidal frequencies (e.g., Arbic et al., 2022; Luecke et al., 2020; Müller et al., 2015; Savage et al., 2017). However, these studies have not specifically focused on tidally generated low‐mode NLIW, which are the target of this paper.…”
Section: Introductionmentioning
confidence: 99%